2002
DOI: 10.1002/gcc.10144
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of the expression of EVI1 and its presumptive antagonist, MDS1/EVI1, in patients with myeloid leukemia

Abstract: The EVI1 gene in chromosome band 3q26 exhibits a number of properties consistent with a role as an oncogene, and its expression is activated in most myeloid leukemia patients with, as well as in a minority of patients without, 3q26 rearrangements. A splice variant of this gene, MDS1/EVI1, acts as its antagonist at least in some tissue culture assays. We established real-time quantitative reverse transcriptase polymerase chain reaction (RTQ-RT-PCR) assays for these mRNA variants to compare their expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
61
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 36 publications
2
61
1
Order By: Relevance
“…However, our experiments showed a strong expression of MEL1 and cMEL in the heart, lung, kidney and pancreas, which should have been easily detected by Mochizuki et al (Figure 3b). Interestingly, a recent report showed the same profile expression in the analysis of MDS1/EVI1 (PR positive) versus cEVI1, a region common to MDS1/ EVI1 and EVI1 (PR negative type), using a similar experimental design (Vinatzer et al, 2003). The expression of both genes was stronger in the same tissues, with the only exception of placenta, where MDS1-EVI1 and cEVI1 are highly expressed, whereas MEL1 and cMEL are poorly expressed.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…However, our experiments showed a strong expression of MEL1 and cMEL in the heart, lung, kidney and pancreas, which should have been easily detected by Mochizuki et al (Figure 3b). Interestingly, a recent report showed the same profile expression in the analysis of MDS1/EVI1 (PR positive) versus cEVI1, a region common to MDS1/ EVI1 and EVI1 (PR negative type), using a similar experimental design (Vinatzer et al, 2003). The expression of both genes was stronger in the same tissues, with the only exception of placenta, where MDS1-EVI1 and cEVI1 are highly expressed, whereas MEL1 and cMEL are poorly expressed.…”
mentioning
confidence: 67%
“…However, a review of the literature shows that not all members of the PRdomain family work in the same way. Two recent studies detected in 17/21 (81%) patients with t(3;3) or inv(3) that high EVI1 expression was associated with high MDS1-EVI1 expression, the form with the PR domain (Barjesteh van Waalwijk van Doorn- Khosrovani et al, 2003;Vinatzer et al, 2003). Moreover, lack of expression of the PR-lacking form EVI1 has been reported in several cases with syndrome 3q21q26 (Fichelson et al, 1992;Morishita et al, 1992;Soderholm et al, 1997;Langabeer et al, 2001), suggesting that the molecular mechanism of leukemogenesis is not the same in all patients.…”
mentioning
confidence: 99%
“…5 Studies of RIZ, MDS-EVI1, MEL1 and BLIMP-1 have revealed that a variety of tumour types often overexpress the PR domain-negative product, relative to the fulllength protein. 4,5,7,9 It is tempting to speculate that in our patient, the distal insertion breakpoint abrogated sequences coding for the 5 0 PR domain of PRDM1, thus causing a relative decrease in the proportion of PR-domain-positive product.…”
Section: Figurementioning
confidence: 83%
“…3 In addition, structural rearrangement, mutation and/or aberrant expression of RIZ, MDS-EVI1 and MEL1 have been reported in myeloid malignancies. 4,7,9 PRDM family members share the feature of expressing two protein products that differ in the presence or absence of the PR domain. 5 Studies of RIZ, MDS-EVI1, MEL1 and BLIMP-1 have revealed that a variety of tumour types often overexpress the PR domain-negative product, relative to the fulllength protein.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation